Peningkatan Keterampilan Menulis Teks Drama Menggunakan Media Flipbook Pada Siswa Kelas XI Smk Negeri 7 Medan - Irma Yani Tarigan; Nadra Amalia; Mutiara Sany Hasibuan (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This study aims to improve the ability to write drama texts in class XI students of SMK Negeri 7 Medan using flipbook learning media. This learning media was chosen because it can encourage students to be creative in expressing their ideas in written form. This research is a type of classroom action research (CAR) with the main problem being that students have difficulty expressing their ideas or ideas through writing and are less active in learning. This study consisted of 3 stages, namely pre-cycle, cycle 1 and cycle 2 with a minimum completeness target (KKM) of 75. The research procedures included planning, implementing actions, observing and reflecting. The subjects of this study were students of class XI Hotel 2 at SMK Negeri 7 Medan consisting of 30 students. The research results obtained at the pre-cycle stage were 43.75% completeness, in cycle 1 it increased to 62.35%, and after cycle 2 it increased again to 87.5%. This means that there is an increase in the skills of writing drama scripts using flipbook media, so that this media is effectively used to write drama scripts.